Biomimicry: New Natures, New Enclosures. (January 2015) - Goldstein, Jesse; Johnson, Elizabeth
Advocates of biomimicry encourage a new industrial paradigm that ostensibly leaves behind the crude violence of Francis Bacon, the domination of nature-as-machine, and a history of toxic production processes that have given rise to a present and coming climate crisis. As part of a broader trend towards the conceptualization and development of a 'bioeconomy', we argue here that biomimicry produces 'nature' in new ways. At face value, these new approaches to valuing nature may seem less violent and exploitative. Yet, new natures can and are tortured in new ways. We argue that biomimicry produces 'nature' through well-worn logics of resource enclosure and privatization, focusing upon two fundamental shifts in how nonhuman life is figured and put to work: (1) the production of nature as intellectual property (as opposed to raw materials); (2) the production of nature as an active subject (as opposed to a passive receptacle or vehicle).